2020
DOI: 10.1017/s0007114520001336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daily consumption of cranberry beverage on insulin sensitivity and modification of cardiovascular risk factors in adults with obesity: a pilot, randomised, placebo-controlled study

Abstract: Cranberries are high in polyphenols, and epidemiological studies have shown that a high-polyphenol diet may reduce risk factors for diabetes and CVD. The present study aimed to determine if short-term cranberry beverage consumption would improve insulin sensitivity and other cardiovascular risk factors. Thirty-five individuals with obesity and with elevated fasting glucose or impaired glucose tolerance participated in a randomised, double-blind, placebo-controlled, parallel-designed pilot trial. Participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 26 publications
(35 reference statements)
1
46
0
1
Order By: Relevance
“…In another study, feeding freeze-dried blueberry powder (1462 mg polyphenols for six weeks) also revealed improvements in insulin sensitivity in adults with metabolic syndrome [ 24 ]. Other feeding trials using cranberry juice polyphenols (~346 mg polyphenols for eight weeks) have also revealed similar [ 25 , 26 ] but some inconsistent results [ 27 ] on insulin resistance and glucoregulation in adults with cardiometabolic risks. In an acute study using a slightly higher dose of strawberries than what was used in our study (40 g strawberry powder; ~three servings of fresh strawberries), Park et al reported a decrease in six-hour postprandial insulin load when compared to the control group in adults with insulin resistance [ 28 ].…”
Section: Discussionmentioning
confidence: 87%
“…In another study, feeding freeze-dried blueberry powder (1462 mg polyphenols for six weeks) also revealed improvements in insulin sensitivity in adults with metabolic syndrome [ 24 ]. Other feeding trials using cranberry juice polyphenols (~346 mg polyphenols for eight weeks) have also revealed similar [ 25 , 26 ] but some inconsistent results [ 27 ] on insulin resistance and glucoregulation in adults with cardiometabolic risks. In an acute study using a slightly higher dose of strawberries than what was used in our study (40 g strawberry powder; ~three servings of fresh strawberries), Park et al reported a decrease in six-hour postprandial insulin load when compared to the control group in adults with insulin resistance [ 28 ].…”
Section: Discussionmentioning
confidence: 87%
“…In an elegant double-blind randomized controlled trial, consumption of 333 mg/day of polyphenols from strawberries and cranberries for 6 weeks improved insulin sensitivity and decreased compensatory insulin hypersecretion in patients with overweight [ 40 ]. Conversely, findings of other studies indicate that daily consumption of cranberry beverages for 8 weeks does not improve insulin sensitivity [ 41 ] and consumption of 140 g/day of blueberries with a carbohydrate breakfast meal does not affect glucose metabolism, nor the gastrointestinal hormones Glucagon Like Peptide 1 (GLP-1), Gastro Inhibitory Peptide, and peptide YY.…”
Section: Specific Dietary Sources Of Polyphenols and Diabetes Riskmentioning
confidence: 97%
“… 6 weeks consumption of strawberry and cranberry extract was associated to significant improvement in insulin sensitivity and insulin secretion. Hsia DS, et al [ 41 ] Parallel double blind controlled and randomized trial in 35 overweight subjects Evaluate the effect of cranberry consumption on insulin sensitivity, glucose tolerance and insulin secretion using the euglycemic iperinsulinemic clamp technique. 8 weeks consumption of cranberry extract has no effects on insulin sensitivity and insulin secretion.…”
Section: Table A1mentioning
confidence: 99%
“…Several studies confirmed that cranberries bioactive compounds have anti-cancer and antimutagenic activities (Prasain, Grubbs, & Barnes, 2020;Howell, 2020). Recently Hsia et al, (2020) investigated that whether consumption of cranberry beverage would improve insulin sensitivity and other cardiovascular complications and reported that daily consumption for 8 weeks may not impact insulin sensitivity but could be helpful in lowering triglycerides and alters some oxidative stress biomarkers in obese individuals with a proinflammatory state (Hsia, Zhang, Beyl, Greenway, & Khoo, 2020). Chew et al, (2019) reported the health benefits of cranberry beverage consumption on gluco regulation, oxidative damage, inflammation, and lipid metabolism in healthy overweight humans (Chew et al, 2019).…”
Section: Health Benefitsmentioning
confidence: 92%